Experiences, acceptability and barriers to calcium supplementation during pregnancy in Dar es Salaam, Tanzania - Emmy O. Metta; Alfa Muhihi; Heavenlight A. Paulo; Christopher R. Sudfeld; Anna Kaale; Nandita Perumal; Mary Mwanyika‐Sando; Ndeniria O. Swai; Christopher P. Duggan; Honorati Masanja; Blair J. Wylie; Andrea B. Pembe; et al. (Maternal and Child Nutrition)
Abstract Calcium supplementation in pregnancy is recommended in contexts with low dietary calcium intake to reduce the risk of pre‐eclampsia and its complications. The World Health Organisation suggested high‐dose calcium supplementation (1500–2000 mg/day), divided into three doses and taken at different times from daily iron‐folic supplements. We conducted a mixed methods evaluation study to assess experiences, acceptability and barriers to high‐dose calcium supplementation from the perspectives of pregnant women and antenatal health care providers at two public health facilities in Dar es Salaam, Tanzania. Descriptive statistics and thematic analysis were used to characterise acceptability, barriers and overall experiences of using high‐dose calcium supplementation. Pregnant women in the cohort were aged 19–41 years, with 32.4% being primiparous. The proportion of pregnant women who liked calcium supplements ‘a lot’ decreased from 50.2% at the first visit to 31.8% at the last antenatal follow‐up visit. Adherence was 71.3% (interquartile range: 50.5%, 89.3%), with only 24.0% of the participants taking 90% or more of the required supplements. Although participants expressed positive attitudes towards using calcium supplements, they also voiced concerns about the large size, side effects, the potential to forget and the burden of taking calcium supplements three times per day. Antenatal health care providers also affirmed the high burden of taking calcium supplements in addition to iron‐folic acid supplements. Participants expressed the acceptability of using calcium supplements during pregnancy, but adherence to three doses per day posed challenges to pregnant women. Reducing the number of calcium supplement doses per day may improve adherence.